Analysis on the effect of land use changes on flooding using SCS method and GIS / Janmaizatulriah Jani, Wardah Tahir and Marfiah Abd. Wahid - Jani, Janmaizatulriah; Tahir, Wardah; Abd. Wahid, Marfiah (Institute of Research, Development and Commercialisation (IRDC), 2007)
The research investigated the effect of land use changes on flood estimation by focusing on a widely used method developed by the US Soil Conservation Services, namely SCS Curve Number method. This method was developed to estimate the peak flow and flood hydrograph based on several parameters, one of it is known as the Curve Number (CN). The CN which can be measured effectively using GIS is an indirect measure of soil potential storage and is dependent on the land use. The research explored the feasibility of the method to Malaysian catchments by firstly, analysed the CN in a small urban catchment of UiTM campus at Shah Alam and secondly compared the hydrograph calculated by the method with the observed ones. The results indicated a close proximity of the CN values obtained from the observed rainfall runoff and the values published by the US SCS (around 8 % difference). In addition, comparison between observed unit hydrographs and SCS unit hydrographs for the same rainfall duration indicated that the estimated values of peak discharge from the synthetic method were not very far from the observed values. Finally, it was shown that changes in land use especially during urbanization process would increase the peak flow, hence increase the possibility of flooding.